2000
DOI: 10.1021/jm990620e
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding, Solubility, and Partitioning Characteristics of Extended Lexitropsins

Abstract: Four new ligands that bind to the minor groove of DNA have been designed, synthesized, and evaluated by DNA footprinting. Two of the ligands are polyamides containing central regions with five or six N-methylpyrrole units, conferring hydrophobicity and good binding affinity but without retaining the correct spacing for hydrogen bonding in the base of the minor groove. The two remaining ligands have central regions which are head-to-head-linked polyamides, in which the linker is designed to improve the phasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…1A ). Many head‐to‐head polyamide molecules have been shown to bind to the A/T rich minor groove [14,15]. It was shown that GL020924 specifically inhibited expression of an engineered cyclin D1 promoter in MCF7 breast cancer cells by competing for promoter binding of transcription factors [16].…”
Section: Introductionmentioning
confidence: 99%
“…1A ). Many head‐to‐head polyamide molecules have been shown to bind to the A/T rich minor groove [14,15]. It was shown that GL020924 specifically inhibited expression of an engineered cyclin D1 promoter in MCF7 breast cancer cells by competing for promoter binding of transcription factors [16].…”
Section: Introductionmentioning
confidence: 99%
“…The pentamethylenic carboxamido linker between the oligopyrrolecarboxamide and the phenanthridine moieties was introduced into the oligopyrrole before condensation with the two chromophores. The fully protected amino oligopyrrolecarboxamide ester 15 was obtained by peptide condensation of the amino ester 12 and 6‐ tert ‐butyloxycarbonylaminohexanoic acid ( 14 ), which were respectively synthesized by reduction of the nitro derivative 11 35 and acylation of the commercially available 6‐aminohexanoic acid ( 13 ). Saponification of the ester 15 afforded the acid 16 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl 1‐methyl‐4‐[1‐methyl‐4‐[(5‐ tert ‐butyloxycarbonylaminopentyl)carboxamido]pyrrole‐2‐carboxamido]pyrrole‐2‐carboxylate (15) : A suspension of nitro compound 11 35 (2.08 g, 6.5 mmol) in MeOH (600 mL) was hydrogenated for 5 h at room temperature under a 5‐bar pressure in the presence of 5 % Pd on activated charcoal (1 g). The catalyst was then removed by filtration, and the MeOH eliminated under reduced pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Many analogs are known in which this group has been replaced with related structures that modify binding affinities,[44], [99], [101][102] and significant changes in this region have been tolerated, for example some of the metal complex-lexitropsin conjugates described in the introduction [55], [60], [65], [72]. However, the reduction in binding affinity for Py-Py-Py (the lexitropsin scaffold of interest here) when the N -formamido moiety is removed is smaller than for other lexitropsins (one order of magnitude, from ca .…”
Section: Discussionmentioning
confidence: 99%